New energy technology innovation and sustainable economic development in the complex scientific environment - Dongxin Li; Aidi Ge (Energy Reports, 2023)
Energy is the material basis of national development, which supports national economic development. With the sustained and rapid economic growth, the energy problem has become the bottleneck hindering sustainable economic and social development, and countries around the world are paying attention to its impact. The development and utilization of New Energy (NE) are inseparable from the support of technological innovation. Technological innovation is an important part of technological philosophy in technological philosophy and the embodiment of value theory. At the current stage of NE economic and ecological development, the contradiction of social values can be solved, because these contradictions can be solved through technological innovation” has been added to the article. To some extent, NE technologies are becoming a new basis for influencing the global pattern and human development. The research on the impact of technological innovation on energy is also helpful to study the impact of science and technology on society. Therefore, this paper studied the relationship between energy technology innovation and economic sustainability by analyzing the characteristics, elements, and challenges of NE technology innovation. Finally, the corresponding implementation strategy was optimized according to the current situation of the NE industry. The resource utilization rate, energy system perfection, and economic benefits after NE technology innovation in complex environment were higher than those before technology innovation. Among them, the resource utilization rate after NE technology innovation was 12.3% higher than that before NE technology innovation; the degree of energy system perfection after NE technology innovation was 9.4% higher than that before NE technology innovation; the economic benefit after NE technology innovation was 9.4% higher than that before NE technology innovation. In short, energy technology innovation was closely related to economic sustainability.